Two 2-D multifunctional cobalt(ii) compounds: field-induced single-ion magnetism and catalytic oxidation of benzylic C–H bonds. Issue 7 (25th January 2017) - Ma, Ranran; Chen, Zhiwei; Cao, Fan; Wang, Suna; Huang, Xianqiang; Li, Yunwu; Lu, Jing; Li, Dacheng; Dou, Jianmin
Abstract : Two 2-D multifunctional cobalt(ii ) compounds were reported with both field-induced single-ion magnetism and catalytic oxidation of benzylic C–H bonds. Abstract : Two cobalt(ii ) compounds, namely, {[Co(HL)(bpy)(H2 O)2 ]·DMF} n (1 ), and {[Co(HL)(bpe)]·0.5bpe} n (2 ) (H3 L = 1, 3-bis(2-carboxylphenoxy)benzoic acid, bpy = 4, 4′-bipyridine, bpe = 4, 4′-vinylenedipyridine), have been synthesized using cobalt(ii ) transition metal salt with phenolic carboxylic acid and different N-donor ligands. The compounds were fully characterized by elemental analysis, infrared spectroscopy (IR), single crystal X-ray diffraction analysis, and thermogravimetric analysis (TGA). Both compounds exhibit 2-D (4, 4)-sql networks but with a wavelike and a double layered arrangement, respectively. Remarkably, these two compounds not only exhibit field-induced single-ion relaxation magnetization but also exceptional catalytic activities of benzylic C–H oxidation (conv. 90.3–99%; sele. 98.1–99%).